Identification of a novel, membrane-associated neuronal kinase, cyclin-dependent kinase 5/p35-regulated kinase. - MCLOUGHLIN, DECLAN (The Society for Neuroscience, 2003)
Here we characterize a novel neuronal kinase, cyclin-dependent kinase 5 (cdk5)/p35-regulated kinase (cprk). Cprk is a member of a previously undescribed family of kinases that are predicted to contain two N-terminal membrane-spanning domains and a long C terminus, which harbors a dual-specificity serine/threonine/tyrosine kinase domain. Cprk was isolated in a yeast two-hybrid screen using the neuronal cdk5 activator p35 as "bait." Cprk interacts with p35 in the yeast-two hybrid system, binds to p35 in glutathione S-transferase fusion pull-down assays, and colocalizes with p35 in cultured neurons and transfected cells. In these cells, cprk is present with p35 in the Golgi apparatus. Cprk is expressed in a number of tissues but is enriched in brain and muscle and within the brain is found in a wide range of neuronal populations. Cprk displays catalytic activity in in vitro kinase assays and is itself phosphorylated by cdk5/p35. Cdk5/p35 inhibits cprk activity. Cdk5/p35 may therefore regulate cprk function in the brain.
PUBLISHED
Keywords: cdk5; p35; tau; neurofilament; Alzheimer's disease; amyotrophic lateral sclerosis